2021
DOI: 10.31436/imjm.v20i4.1693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Effect of Prophylactic Intravenous Dexamethasone in Post Spinal Shivering: A Single Centre Randomised Controlled Study

Abstract: Introduction: Shivering is a common side effect of central neuraxial anaesthesia. Intravenous pethidine is commonly used in reducing shivering but has been associated with significant opioid side effects. Dexamethasone as a powerful anti-inflammatory and analgesia agent is postulated to inhibit inflammatory mediators’ release thus inhibiting central thermoregulatory centre, potentially attenuating post spinal shivering.  This double-blinded randomised controlled study was to determine the ability of intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…While 2 studies evaluated the effect of prophylactic steroids on shivering in patients undergoing cardiac surgery, 7,27 19 studies were in patients undergoing various noncardiac surgeries, 15,26,28–39,42–46 and 4 studies were performed in women undergoing cesarean deliveries. 14,40,41,47 Perioperative shivering was the primary outcome in 21 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While 2 studies evaluated the effect of prophylactic steroids on shivering in patients undergoing cardiac surgery, 7,27 19 studies were in patients undergoing various noncardiac surgeries, 15,26,28–39,42–46 and 4 studies were performed in women undergoing cesarean deliveries. 14,40,41,47 Perioperative shivering was the primary outcome in 21 studies.…”
Section: Resultsmentioning
confidence: 99%
“…48 Another study was excluded because the authors only evaluated the severity risk and not the risk of overall shivering. 49 While 2 studies evaluated the effect of prophylactic steroids on shivering in patients undergoing cardiac surgery, 7,27 19 studies were in patients undergoing various noncardiac surgeries, 15,26,[28][29][30][31][32][33][34][35][36][37][38][39][42][43][44][45][46] and 4 studies were performed in women undergoing cesarean deliveries. 14,40,41,47 Perioperative shivering was the primary outcome in 21 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Another RCT study done in Malaysia showed that administration of dexamethasone is very effective in maintaining body temperature and the reductions of the incidence of shivering in patients undergoing surgery with spinal anesthesia. 33 The Role of Magnesium Sulphate in Prevention and Management of Post-Spinal Shivering Magnesium sulfate (MgSO 4 ) is an inorganic salt and non-competitive antagonist of N-methyl-D aspartate (NMDA) receptors with a good safety profile and neuroprotective properties under the condition of hypothermia. It plays a big role in suppressing the postoperative shivering through a central effect by reducing the shivering threshold and additionally blocks NMDA receptors, decreasing norepinephrine and 5-HT receptor which both play a role in thermoregulation.…”
Section: Dexamethasone Role In Prevention and Management Of Shiveringmentioning
confidence: 99%
“…[ 1 ] Studies have demonstrated that the incidence of shivering associated with central neuraxial block is at the range 40% to 70%. [ 2 , 3 ] The incidence of shivering in obstetric patients with neuraxial blockade is between 40% to 60%. [ 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%